Beyond the positive reinforcement of aggression: Peers' acceptance of aggression promotes aggression via external control beliefs. (January 2018) - Jung, Janis; Krahé, Barbara; Busching, Robert
Being surrounded by peers who are accepting of aggression is a significant predictor of the development and persistence of aggression in childhood and adolescence. Whereas past research has focused on social reinforcement mechanisms as the underlying processes, the present longitudinal study analysed the role of external control beliefs as an additional mediator explaining the link between peers' acceptance of aggression and the development of aggressive behaviour. Drawing on a large community sample of N = 1, 466 male and female children and adolescents from Germany aged between 10 and 18 years, results of latent structural equation modeling were consistent with the hypotheses that peer acceptance of aggression would predict external control beliefs in the social domain, which in turn, should predict aggressive behaviour over time. Additional multigroup analyses showed that the predicted pathways were consistent across gender and age groups.